(untitled) (PJDOL, 2023)
E-learning is an emerging form of organizational learning to train and educate employees in, knowledge-based organizations. Whereas, the motivation to transfer those learned skills is of colossal prominence in training and operative knowledge management. This study is, therefore, intended to discover the structural connotation of operative aspects (internal value, sense of psychological happiness, learning environment, e-learner achievement) and skill transfer of e-learner. The onlinesurvey was performed for a collection of 213 employed e-learners of Virtual University, who were registered in three different courses of management sciences. Data was evaluated by using AMOS and SPSS. SEM results established that the structural connotation among e-learner’s sense of psychological happiness & motivation for skill transfer, internal value & e-learner’s achievement, is considerably confirmative. Nevertheless, the study instituted a feeble structural association between the learning environment and the e-learner’s motivation for skill transfer.